2021
DOI: 10.1038/s41598-021-81298-1
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of bone marrow FDG uptake in patients with gynecological cancer

Abstract: We investigated the prognostic significance and the underlying mechanism of increased bone marrow (BM) 2-(18F) fluoro-2-deoxy-D-glucose as a tracer (FDG)-uptake in patients with gynecological cancer. A list of patients diagnosed with cervical, endometrial, and ovarian cancer from January 2008 to December 2014 were identified. Then, through chart reviews, 559 patients who underwent staging by FDG-positron emission tomography (PET)/computed tomography (CT) and subsequent surgical resection were identified, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…Consistent with the findings of in vitro and in vivo experiments, an increase in the number of circulating or tumor-infiltrating MDSCs was associated with a decrease in the number of tumor-infiltrating CD8 + T cells [ 29 , 31 , 35 ]. An increased number of MDSCs was also associated with unfavorable clinicopathological parameters, including advanced clinical stage [ 35 ], visceral or lymph node metastases [ 22 , 35 , 38 ], deep stromal invasion [ 35 ], poor sensitivity to anticancer treatments (radiotherapy or chemotherapy) [ 21 , 28 , 29 ], high recurrence rate [ 35 ], and short survival [ 21 , 28 , 29 , 31 ] in patients with uterine cervical and endometrial cancers ( Table 2 ). Moreover, it has been recently demonstrated that MDSC-mediated premetastatic niche formation in the lymph nodes induces 18F-fluorodeoxyglucose (FDG) uptake during FDG-positron emission tomography/computed tomography and causes false-positive detection of nodal metastasis [ 23 ].…”
Section: Mdscs In Patients With Uterine Cervical and Endometrial Cancerssupporting
confidence: 84%
See 4 more Smart Citations
“…Consistent with the findings of in vitro and in vivo experiments, an increase in the number of circulating or tumor-infiltrating MDSCs was associated with a decrease in the number of tumor-infiltrating CD8 + T cells [ 29 , 31 , 35 ]. An increased number of MDSCs was also associated with unfavorable clinicopathological parameters, including advanced clinical stage [ 35 ], visceral or lymph node metastases [ 22 , 35 , 38 ], deep stromal invasion [ 35 ], poor sensitivity to anticancer treatments (radiotherapy or chemotherapy) [ 21 , 28 , 29 ], high recurrence rate [ 35 ], and short survival [ 21 , 28 , 29 , 31 ] in patients with uterine cervical and endometrial cancers ( Table 2 ). Moreover, it has been recently demonstrated that MDSC-mediated premetastatic niche formation in the lymph nodes induces 18F-fluorodeoxyglucose (FDG) uptake during FDG-positron emission tomography/computed tomography and causes false-positive detection of nodal metastasis [ 23 ].…”
Section: Mdscs In Patients With Uterine Cervical and Endometrial Cancerssupporting
confidence: 84%
“…Further, a co-culture experiment indicated that MDSCs in patients with cervical cancer can be induced by tumor-derived factors [ 27 ]. Factors that induced MDSC in mice models of uterine endometrial and cervical cancer include tumor-derived G-CSF, IL-6, estradiol (E2), and Swainsonine [ 21 , 22 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. MDSCs obtained from these experimental models have been shown to inhibit the activity of CD8 + T cells [ 21 , 22 , 28 , 29 , 30 , 31 , 35 ], stimulate tumor angiogenesis [ 21 ], contribute to premetastatic niche formation [ 22 , 23 ], and increase the stem-like properties of cancer cells [ 29 , 30 ], all of which can promote tumor progression by facilitating tumor growth, metastasis [ 22 ], and resistance to anticancer treatments, including chemotherapy and radiotherapy [ 21 , 28 ].…”
Section: Mdscs In Patients With Uterine Cervical and Endometrial Cancersmentioning
confidence: 99%
See 3 more Smart Citations